Penguatan Peran POLRI dalam Implementasi Hukum Pidana Internasional - Prof. Dr. Iza Fadri (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
Changes and developments in the national, regional, and global environment have triggered the rapid development of transnational crime, in this context, the Indonesian National Police (Polri) with the authority to act as state apparatus and law enforcer is the spearhead and front guard of the criminal justice system in eradicating transnational crime. Related to the foregoing, the applicability of International Criminal Law and its application in Indonesia is still an unresolved problem. In connection with the above, in terms of reviewing and analyzing related to the prospects of international criminal law and challenges to the Indonesian National Police, the author use normative juridical research methods using library research. The Juridical-Normative research method is a research method that places legal principles and legal rules as a touchstone to assess whether there was actually a violation or not. So, it can be concluded that there is a need to strengthen and develop international criminal law which is supported by comparative studies and activities in the framework of comparative law or comparative study of international criminal law studies at S1 STIK-PTIK. In the Elucidation of Article 7 of the Human Rights Court Law, it is stated that “the crimes of genocide and crimes against humans in this provision are in accordance with the Rome Statute of the International Criminal Court (Article 6 and Article 7)”. This provision raises the consequence that the legal spirit, interpretation, elements, and application must follow and comply with the provisions contained in the ICC Statute. In the course of the following, several serious human rights violations have been examined and tried based on the Human Rights Court Law with the establishment of an Ad Hoc Human Rights Court, such as the East Timor Post-Ballot case and the Abepura case.